Proyecto para el desarrollo de habilidades sociales en niños y adolescentes del Centro de Acogida Temporal Mi Caleta. - Quispe Cruz, Jéssica Maribel (2016)
This project comes after carrying out several months of pre-professional practices and a diagnosis in the Fundacion Proyecto Salesiano “Chicos de la Calle”, specifically program “Mi Caleta”; showing results in children and adolescents had deficits in social skills. Considering the current and subsequent welfare of these guys this project was created to develop and enhance various skills to a better development in society with use of cooperative games. Since being children at risk and vulnerability the playful aspect that is very important in the development of the human being is not taken into account, focusing mainly interest in tasks that allow them to obtain financial means. So, we started from the use of tools such as observation and survey instruments to determine what the deficient skills we continue with workshops applied and finally the results. Is used theory of Lev Vygotsky and Paulo Freire for contrast and complement the validity of using games and specifically cooperative games as a means of developing social skills.